Titanium alloy jaw bone scaffold as well as preparation method and application thereof
By 3D printing of porous titanium alloy scaffolds and using femtosecond laser to form micro-nanoized surface structures, the problems of osteoporosis and insufficient cell adhesion after jaw implantation are solved, and bone integration and healing are achieved significantly It is lifted and provides a new method for repairing jaw defects.
Patent Information
- Application Number
- CN202411189558.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-28
- Publication Date
- 2024-12-31
AI Technical Summary
The existing medical titanium alloys are osteoporosis and loose endophytes after the jaw implantation, and the cell adhesion is weak and the bone integration ability is insufficient.
Porous titanium alloy scaffolds were prepared by 3D printing technology, and micronized surface structure was formed through femtosecond laser technology to reduce elastic modulus and improve cell adhesion.
It effectively reduces the stress shielding effect, promotes bone integration and healing, and improves the long-term stability of titanium alloy stents and the effect of bone defect repair.
Smart Images

Figure CN119215224A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of repair materials, and in particular relates to a titanium alloy jawbone bracket and a preparation method and application thereof. Background Art
[0002] Jaw defects caused by trauma, tumors, infection and developmental malformations have a huge impact on the patient's aesthetics and physiological functions (such as chewing, pronunciation, etc.). At present, autologous bone transplantation is the "gold standard" for repairing jaw defects in clinical practice. However, autologous bone transplantation has high requirements for the tissue of the donor site, and has disadvantages such as limited bone volume, donor site pain, bleeding, infection, opening a second surgical site, difficulty in plasticity, and prolonged operation time. Medical titanium alloy (T i6Al4V) has been used in clinical practice for more than 40 years due to its good mechanical properties, biocompatibility and corrosion resistance, but there are two problems: its elastic modulus (100-140GPa) is still greater than the elastic modulus of bone (1-24GPa), which will cause stress shielding effect, and long-term implantation will easily lead to osteoporosis and implant loosening due to reduced force in bone tissue; in addition, the existing surface treatment methods of medical titanium alloys are mostly sandblasting, and the cell adhesion is weak after implantation in the body, and the bone integration ability needs to be improved. Therefore, it is very necessary to solve the above problems and develop a titanium alloy material that can reduce the stress shielding effect, promote cell adhesion and improve bone integration ability. Summary of the invention
[0003] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a titanium alloy jawbone support and a preparation method and application thereof.
[0004] To achieve the above object, the technical solution adopted by the present invention is:
[0005] A titanium alloy jawbone support comprises a titanium alloy porous support and a micro-nano surface structure formed on the surface of the titanium alloy porous support.
[0006] The cell structure of the titanium alloy porous support is one of diamond type (Di amond, DI), cross-sectional cube type (Truncated Cube, TC), and cube type (Cube, CU).
[0007] The pore diameter of the titanium alloy porous bracket is 600 μm to 900 μm, and the rod diameter is 150 μm to 300 μm.
[0008] The constituent component of the titanium alloy porous bracket is Ti6Al4V.
[0009] The micronized surface structure is one of a periodic surface nano-corrugated structure, a nano-cluster structure, a micro-groove composite periodic surface nano-corrugated structure or a micro-groove composite nano-cluster structure.
[0010] The present invention also includes a method for preparing the titanium alloy jawbone bracket, comprising the following steps: 1) 3D printing a titanium alloy porous bracket; 2) using femtosecond laser technology to form a micro-nano surface structure on the surface of the titanium alloy porous bracket.
[0011] The specific steps of step 1) are as follows: 1.1) constructing a computer-aided design (CAD) model of a titanium alloy porous scaffold using Mimics 21.0 and 3-mat ic 13.0; 1.2) V The titanium alloy porous bracket is prepared by using metal as raw material and laser selective melting technology 3D printing method; preferably, laser melting is carried out in protective nitrogen; 1.3) the printed titanium alloy porous bracket is cleaned to remove the titanium particles and impurities remaining on the surface of the porous titanium alloy bracket; preferably, ultrasonic cleaning is carried out in double distilled water, acetone and 75% ethanol for 30 minutes.
[0012] Preferably, in step 1.2), Ti6Al4 V The metal is in the form of spherical powder with a diameter of 15 to 53 μm.
[0013] The specific steps of step 2) are: use a high-energy industrial integrated ultrafast amplified laser system with a pulse center wavelength of 532nm, a maximum output power of 18.7w, a repetition frequency of 180kH~220kH, a single pulse energy of 93.5μJ, a pulse width of 260fs, and a spot diameter of 3mm±1mm to perform femtosecond laser treatment on the titanium alloy porous bracket obtained in step 1) to obtain a 3D printed titanium alloy jaw bracket with a micro-nano surface structure.
[0014] The present invention also includes an application of the titanium alloy jawbone support as a repair material for oral jawbone defects.
[0015] Compared with the prior art, the present invention has the following beneficial effects:
[0016] The technical solution of the present application combines 3D printing with femtosecond laser, and uses 3D printing technology to construct a titanium alloy porous scaffold. By designing various parameters of the porous structure such as pore shape (cell structure) and pore size, the elastic modulus of the titanium alloy scaffold can be effectively reduced while ensuring sufficient mechanical strength, thereby reducing the stress shielding effect. Suitable pores are also conducive to the growth of new bone tissue and capillaries, forming biological fixation, so that the scaffold and the new bone tissue form a firm mechanical lock, thereby improving the long-term stability of the implant.
[0017] As an interface for interaction with various proteins and cells, the surface structure of the titanium alloy porous scaffold has a significant effect on cell adhesion, bone integration and the degree of bone defect healing. The present application uses a femtosecond laser (FS) to perform micro-nano processing on the surface of the titanium alloy porous scaffold. Its high peak power will cause the material to produce strong nonlinear absorption, and the penetration depth and heat-affected zone on the surface of the material are small. Femtosecond laser can easily realize processing from macroscopic structure to nanoscale structure, construct the micro-nano surface morphology of the titanium alloy scaffold, thereby regulating the roughness, cell proliferation, cell differentiation, etc. of the titanium alloy porous scaffold, and then promote bone integration and bone defect healing.
[0018] In summary, combining 3D printing with femtosecond laser to prepare a 3D printed titanium alloy porous scaffold with a micro-nano surface structure has become a new idea to reduce the stress shielding of titanium alloy scaffolds and improve their bone integration ability. The influence of the mechanical shielding effect is reduced by designing parameters such as the pore shape and pore size of the porous structure. At the same time, femtosecond laser processing is used to construct a micro-nano surface to improve cell adhesion and bone integration ability, providing a new treatment method for the repair of mandibular defects. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The porous stent CAD model of the titanium alloy porous stent with different cell structures and pore sizes according to Example 1 of the present invention;
[0020] Figure 2 The following are the appearance pictures and scanning electron microscope pictures at 30 times magnification of the titanium alloy porous stent in Example 1 of the present invention. (A) Appearance picture for cytological research, (B) Appearance picture for mechanical research, (C) Scanning electron microscope picture at 30 times magnification;
[0021] Figure 3 1 is a stress-strain diagram of each group of porous titanium alloy stents in Example 1 of the present invention;
[0022] Figure 4 The uniaxial compression ratchet test results of the porous titanium alloy stent of the 0.9 pore size group in Example 1 of the present invention are shown; (A) DI 0.9 stent stress-strain hysteresis curve (B) CU 0.9 stent stress-strain hysteresis curve (C) TC 0.9 stent stress-strain hysteresis curve (D) The influence of the cell structure on the ratchet behavior;
[0023] Figure 5 The figure is the expression of osteogenic genes of MC3T3-E1 osteoblasts inoculated on the titanium alloy scaffolds of each group in Example 1 after 14 days of osteogenic induction. (A) RUNX2, (B) OCN, (C) OPN, (D) COL-1.
[0024] Figure 6 It is the electron microscope image of the surface morphology of each group in Example 2 of the present invention and the micro-nano structure produced by treating the titanium alloy with different femtosecond laser parameters in Control Example 1 (AM).
[0025] Figure 7 It is the cell morphology diagram of the surface morphology of MC3T3-E1 osteoblasts cultured in each group of Example 2 of the present invention and Control Example 1 (AM) after 24 hours.
[0026] Figure 8 It is the CCK-8 activity detection of MC3T3-E1 osteoblasts adhesion and proliferation on the surface morphology of each group in Example 2 and the titanium alloy surface morphology of Control Example 1 (AM).
[0027] Fig. 9 The osteogenic gene expression of MC3T3-E1 osteoblasts inoculated on the surface morphology of each group in Example 2 and the surface morphology of titanium alloy in Control Example 1 (AM) after 14 days of osteogenic induction. (A) RUNX2, (B) OCN, (C) OPN, (D) COL-1. (Real ime-PCR detection).
[0028] Fig.10 Example 3 and Control Example 2 were implanted into the mandibular bones of New Zealand rabbits and then removed at 4 and 12 weeks. The basic bone parameters related to the area around the scaffold were analyzed (detected by Micro-CT). Note: bone volume fraction (BV / TV); bone mineral density (BMD). DETAILED DESCRIPTION
[0029] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and the best embodiments.
[0030] A titanium alloy jawbone support comprises a titanium alloy porous support and a micro-nano surface structure formed on the surface of the titanium alloy porous support.
[0031] The cell structure of the titanium alloy porous support is one of diamond type (Diamond, DI), cross-sectional cube type (Truncated Cube, TC), and cube type (Cube, CU).
[0032] The pore diameter of the titanium alloy porous stent is 600 μm to 900 μm, and the rod diameter is 150 μm to 300 μm.
[0033] The constituent component of the titanium alloy porous bracket is Ti6Al4V.
[0034] The micronized surface structure is one of a periodic surface nano-corrugated structure experimental group, a nano-cluster experimental group, a micro-groove composite periodic surface nano-corrugated structure experimental group or a micro-groove composite nano-cluster experimental group.
[0035] The present invention also includes a method for preparing the titanium alloy jawbone bracket, comprising the following steps: 1) 3D printing a titanium alloy porous bracket; 1.1) constructing a computer-aided design (CAD) model of the titanium alloy porous bracket through Mimics21.0 and 3-mat 13.0; 1.2) using Ti6Al4V metal (spherical powder with a diameter of 15 to 53 μm) as a raw material, the titanium alloy porous bracket is prepared by a laser selective melting technology 3D printing method; preferably, the laser melting is carried out in protective nitrogen; 1.3) ultrasonically cleaning the printed titanium alloy porous bracket in double distilled water, acetone, and 75% ethanol for 30 minutes in turn to remove the titanium particles and impurities remaining on the surface of the porous titanium alloy bracket.
[0036] 2) A femtosecond laser technology is used to form a micro-nano surface structure on the surface of the titanium alloy porous bracket. A high-energy industrial integrated ultrafast amplification laser system with a pulse center wavelength of 532nm, a maximum output power of 18.7w, a repetition frequency of 180kH~220kH, a single pulse energy of 93.5μJ, a pulse width of 260fs, and a spot diameter of 3mm±1mm is used to perform femtosecond laser treatment on the titanium alloy porous bracket obtained in step 1) to obtain a 3D printed titanium alloy jaw bracket with a micro-nano surface structure. The performance of a single titanium alloy porous bracket and a single femtosecond laser treatment performance are studied using Examples 1 and 2 respectively. In this way, the performance of the titanium alloy porous bracket and the micro-nano surface structure are studied, and Example 3 is used to combine the preferred examples of Examples 1 and 2 for illustration.
[0037] Example 1
[0038] The method for 3D printing a titanium alloy porous scaffold specifically comprises the following steps: 1.1) constructing a CAD model of a titanium alloy porous scaffold by using Mimics21.0 and 3-matic13.0; obtaining a titanium alloy porous scaffold model by arraying a single cell structure, performing Boolean operations on the titanium alloy porous scaffold using a cylinder, and finally obtaining a titanium alloy porous scaffold model of different cell structure types;
[0039] A total of 6 groups of titanium alloy porous stents were designed ( Figure 1), where the cell structures are diamond (DI), trunked cube (TC), and cube (CU), and the average pore diameters of the scaffolds are 600 μm and 900 μm, corresponding to DI 0.6, TC 0.6, CU 0.6, DI 0.9, TC 0.9, and CU 0.9, respectively; the rod diameter of each group of scaffolds is 200 μm.
[0040] 1.2) Using Ti6Al4V metal (spherical powder with a diameter of 15 to 53 μm) as raw material, the titanium alloy porous scaffold is prepared by a laser selective melting technology 3D printing method; the laser melting is performed in a protective nitrogen atmosphere;
[0041] The designed titanium alloy porous scaffold model was converted into STP format and imported into the 3D printing equipment (Plite S310, Xi'an, Shaanxi, China). The printing material was Ti6Al4V metal powder, and the laser selective melting process was used for printing. The laser melting was carried out in protective nitrogen. The diameter of the spherical Ti6Al4V metal powder was 15μm to 53μm. The printing parameters were set as follows: laser radiation power 130w, laser diameter 0.1mm, scanning spacing 30μm, scanning speed 1200m / s, spot compensation 0.02mm, and single-layer forming thickness 30μm.
[0042] 1.3) The printed titanium alloy porous scaffold was ultrasonically cleaned in double distilled water, acetone, and 75% ethanol for 30 minutes to remove the titanium particles and impurities remaining on the surface of the porous titanium alloy scaffold to obtain a titanium alloy porous scaffold such as Figure 2 Shown, from Figure 2 It can be seen that Example 1 of the present invention has the same diamond shape, cube cross-section and cubic cell structure as the design, the pore size of the bracket is uniform, and a large number of titanium alloy particles adhered to the surface of the bracket can also be observed.
[0043] Figure 3 The stress-strain diagrams of each group of porous titanium alloy scaffolds are shown. The results show that the elastic modulus of the six groups of scaffolds is in the range of 0.247-1.870GPa, which meets the normal elastic modulus range (0.1-4.5GPa) that matches bone tissue. In terms of compression performance, DI performs best, followed by TC, and CU is the worst.
[0044] Figure 4 The uniaxial compression ratchet test results of the porous titanium alloy stent of the 0.9 pore size group are shown: (A) DI 0.9 stent stress-strain hysteresis curve (B) CU 0.9 stent stress-strain hysteresis curve (C) TC 0.9 stent stress-strain hysteresis curve (D) The influence of the cell structure on the ratchet behavior; Figure 4It can be seen that the TC 0.9 stent has the best compression ratchet fatigue performance, followed by the DI 0.9 stent, and the worst is the CU 0.9 stent.
[0045] Figure 5 The osteogenic gene expression of MC3T3-E1 osteoblasts was shown after 14 days of osteogenic induction after MC3T3-E1 osteoblasts were inoculated on titanium alloy scaffolds in each group. (A) RUNX2, (B) OCN, (C) OPN, (D) COL-1, according to Figure 5 It can be seen that the expression levels of osteogenic genes in MC3T3-E1 cells inoculated at DI0.9 and TC 0.9 are higher.
[0046] Therefore, the titanium alloy porous scaffold with DI 0.9 and TC 0.9 was selected for subsequent research description.
[0047] Example 2
[0048] The formation of the micro-nano surface structure includes the following steps: 1) 3D printing a titanium alloy sheet whose size is designed to be 10mm*10mm*0.8mm; specifically including the following steps: using Ti6Al4V metal (spherical powder with a diameter of 15 to 53μm) as a raw material, the titanium alloy sheet is prepared by a laser selective melting technology 3D printing method; the laser melting is carried out in a protective nitrogen atmosphere; the printed titanium alloy sheet is ultrasonically cleaned in double distilled water, acetone, and 75% ethanol for 30 minutes in turn to remove the titanium particles and impurities remaining on the surface of the titanium alloy sheet.
[0049] 2) Femtosecond laser treatment was performed on the surface of the titanium alloy sheet, and a series of titanium alloy sheets with different micro-nano surface structures were obtained by changing the femtosecond laser parameters (Table 1 shows the femtosecond laser printing parameters corresponding to each surface morphology): periodic surface nanocorrugated structures (Laser-i nduced periodic surface structures, L), nanocluster structures (Nanocluster, N), microgroove composite periodic surface nanocorrugated structures (Microchanne l+Laser-i nduced periodic surface structures, ML) and microgroove composite nanocluster structures (Microchanne l+Nanocluster, MN).
[0050] Table 1
[0051]
[0052] Note: The parameters of the ML and MN groups are to print MC first, and then print L and N respectively without moving the sample.
[0053] A titanium alloy sheet without femtosecond laser processing (Additive Manufacturing, AM) is used as control example 1.
[0054] Figure 6 The surface morphology of each group of Example 2 of the present invention and the micro-nano structure electron microscope image produced by treating titanium alloy with different femtosecond laser parameters in Control Example 1 (AM) show that the present invention successfully constructs two kinds of nano surfaces (periodic surface nano-corrugated structure, nano-cluster structure) and two kinds of micro-nano composite surfaces (micro-groove composite periodic surface nano-corrugated structure, micro-groove composite nano-cluster structure). The period of Group L is 600nm, and the mastoid columnar structure and irregular holes can be observed on the surface of Group N. The ridge width of the micro-groove is about 40μm, and the groove width is about 25μm.
[0055] Table 2 shows the roughness of the titanium alloy surface in each group, which is a comparison of the surface morphology of each group in Example 2 of the present invention and the roughness of the control example 1 (AM). (Detection by laser confocal microscope) As can be seen from Table 1, the Sa results are ML>MN>L>N>AM. This shows that the surface roughness of the titanium alloy can be increased by femtosecond laser treatment. In addition, the roughness of the composite group is greater than that of the simple treatment group, indicating that complex surface morphology will increase the roughness.
[0056] Table 2
[0057]
[0058] Figure 7 The surface morphology of MC3T3-E1 osteoblasts cultured in each group of Example 2 of the present invention and the cell morphology of Control Example 1 (AM) after 24 hours (Scanning electron microscope observation, 150 and 1500 times). Figure 7 It can be seen that both Example 2 and Control Example 1 (AM) have good biodegradability, and the morphologies of the two groups ML and MN are more conducive to inducing cells to grow and crawl along the microgrooves, and the cell morphology is elongated.
[0059] Figure 8 The CCK-8 activity test of MC3T3-E1 osteoblasts adhering and proliferating on the surface morphologies of each group in Example 2 and the titanium alloy surface morphologies of Control Example 1 (AM) was performed. Figure 8 It can be seen that the titanium alloy stents with surface morphologies of Example 2 and Control Example 1 (AM) have good biocompatibility. On the fifth day of incubation, differences began to appear among the groups, and MN was most conducive to cell proliferation.
[0060] Fig. 9The osteogenic gene expression of MC3T3-E1 osteoblasts inoculated on the surface morphology of each group in Example 2 and the surface morphology of titanium alloy in Control Example 1 (AM) after 14 days of osteogenic induction. (A) RUNX2, (B) OCN, (C) OPN, (D) COL-1. (Real ime-PCR detection). Fig. 9 It can be seen that the MC3T3-E1 cells inoculated in MN and ML expressed higher levels of osteogenic genes, and therefore had stronger osteoinductive properties.
[0061] Therefore, subsequent experiments were conducted with two groups of ML and MN combined with the titanium alloy porous scaffolds with DI 0.9 and TC 0.9 of Example 1.
[0062] Example 3
[0063] A method for preparing a titanium alloy jaw support comprises the following steps:
[0064] 1) 3D printed titanium alloy porous scaffold;
[0065] 1.1) The CAD model of the titanium alloy porous scaffold was constructed by Mimics21.0 and 3-mat i c13.0; two groups of titanium alloy porous scaffolds were designed, in which the cell structures were diamond type (DI) and cross-section cube type (TC), the average diameter of the pores of the scaffolds was 900μm, and the rod diameter of each group of scaffolds was 200μm. The porous scaffold model was obtained by arraying a single cell, and the porous scaffold model was Boolean operated using a cylinder, and finally the titanium alloy porous scaffold models of different cell types were obtained.
[0066] 1.2) Ti6Al4 V Metal (spherical powder with a diameter of 15 to 53 μm) is used as raw material, and the preparation method is a 3D printing method using laser selective melting technology to prepare a titanium alloy porous scaffold; laser melting is performed in a protective nitrogen atmosphere;
[0067] The designed titanium alloy porous scaffold model was converted into STP format and imported into the 3D printing equipment (Plite S310, Xi'an, Shaanxi, China). The printing material was Ti6Al4V metal powder, and the SLM process was used for printing. The laser melting was carried out in protective nitrogen. The diameter of the spherical Ti6Al4V metal powder was 15μm to 53μm. The printing parameters were set as follows: laser radiation power 130w, laser diameter 0.1mm, scanning spacing 30μm, scanning speed 1200m / s, spot compensation 0.02mm, and single-layer forming thickness 30μm.
[0068] 1.3) The printed titanium alloy porous scaffold was ultrasonically cleaned in double distilled water, acetone, and 75% ethanol for 30 minutes in turn to remove the titanium particles and impurities remaining on the surface of the porous titanium alloy scaffold.
[0069] 2) Using femtosecond laser technology to form a micro-nano surface structure on the surface of the titanium alloy porous scaffold. A high-energy industrial integrated ultrafast amplified laser system with a pulse center wavelength of 532nm, a maximum output power of 18.7w, a repetition frequency of 180kH-220kH, a single pulse energy of 93.5μJ, a pulse width of 260fs, and a spot diameter of 3mm±1mm was used to perform femtosecond laser treatment on the titanium alloy porous scaffold obtained in step 1) to obtain a 3D printed titanium alloy jaw scaffold with a micro-nano surface structure.
[0070] By changing the femtosecond laser parameters, the processing method is the same as shown in Table 1 of Example 2, and four groups of titanium alloy stents with different titanium alloy surface morphologies and cellular structures are obtained: microgroove composite periodic surface nano-corrugated structure diamond cellular porous titanium alloy stent (DI ML), microgroove composite nano-cluster structure + diamond cellular porous titanium alloy stent (DIMN); microgroove composite periodic surface nano-corrugated structure + cross-section cubic cellular porous titanium alloy stent (TCML), microgroove composite nano-cluster structure + cross-section cubic cellular porous titanium alloy stent (TCMN).
[0071] A diamond cell porous titanium alloy scaffold (DI) without surface treatment and without femtosecond laser treatment and a cross-sectional cubic cell porous titanium alloy scaffold (TC) without surface treatment are used as control example 2.
[0072] Fig.10 The Example 3 and the Control Example 2 were implanted into the mandible of New Zealand rabbits at 4 weeks and 12 weeks, and the basic bone parameters of the area around the scaffold were analyzed (detected by Micro-CT), Note: Bone volume fraction (BV / TV); Bone mineral density (BMD), from Fig.10 It can be seen that Example 3 has better ability to promote osteogenesis than Control Example 2, and the effects are similar.
[0073] The technical solution of the present application combines 3D printing with femtosecond laser, and uses 3D printing technology to construct a titanium alloy porous scaffold. By designing various parameters of the porous structure such as pore shape (cell structure) and pore size, the elastic modulus of the titanium alloy scaffold can be effectively reduced while ensuring sufficient mechanical strength, thereby reducing the stress shielding effect. Suitable pores are also conducive to the growth of new bone tissue and capillaries, forming biological fixation, so that the scaffold and the new bone tissue form a firm mechanical lock, thereby improving the long-term stability of the implant.
[0074] As an interface for interaction with various proteins and cells, the surface structure of the titanium alloy porous scaffold has a significant effect on cell adhesion, bone integration and the degree of bone defect healing. The present application uses a femtosecond laser (FS) to perform micro-nano processing on the surface of the titanium alloy porous scaffold. Its high peak power will cause the material to produce strong nonlinear absorption, and the penetration depth and heat-affected zone on the surface of the material are small. Femtosecond laser can easily realize processing from macroscopic structure to nanoscale structure, construct the micro-nano surface morphology of the titanium alloy scaffold, thereby regulating the roughness, cell proliferation, cell differentiation, etc. of the titanium alloy porous scaffold, and then promote bone integration and bone defect healing.
[0075] In summary, combining 3D printing with femtosecond laser to prepare a 3D printed titanium alloy stent with a micro-nano structure has become a new idea to reduce the stress shielding of the titanium alloy stent and improve its bone integration ability. The influence of the mechanical shielding effect is reduced by designing parameters such as the pore shape and pore size of the porous structure. At the same time, femtosecond laser processing is used to construct a micro-nano surface to improve cell adhesion and bone integration ability, providing a new treatment method for the repair of mandibular defects.
[0076] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A titanium alloy jaw support, characterized in that: It comprises a titanium alloy porous support and a micro-nano surface structure formed on the surface of the titanium alloy porous support.
2. The titanium alloy jawbone support according to claim 1, characterized in that: The cell structure of the titanium alloy porous support is one of a diamond type, a cross-section cube type and a cubic type.
3. The titanium alloy jawbone support according to claim 1, characterized in that: The pore diameter of the titanium alloy porous bracket is 600 μm to 900 μm, and the rod diameter is 150 μm to 300 μm.
4. The titanium alloy jawbone support according to claim 1, characterized in that: The constituent component of the titanium alloy porous bracket is Ti6Al4V.
5. The titanium alloy jawbone support according to claim 1, characterized in that: The micronized surface structure is one of a periodic surface nano-corrugated structure, a nano-cluster structure, a micro-groove composite periodic surface nano-corrugated structure or a micro-groove composite nano-cluster structure.
6. A method for preparing a titanium alloy jawbone stent according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: 1) 3D printing a titanium alloy porous bracket; 2) using femtosecond laser technology to form a micro-nano surface structure on the surface of the titanium alloy porous bracket.
7. The preparation method according to claim 6, characterized in that: The specific steps of step 1) are: 1.1) constructing a computer-aided design model of a titanium alloy porous scaffold; 1.2) using Ti6Al4 V The titanium alloy porous bracket is prepared by using metal as raw material and laser selective melting technology 3D printing method; preferably, laser melting is carried out in protective nitrogen; 1.3) the printed titanium alloy porous bracket is cleaned to remove the titanium particles and impurities remaining on the surface of the porous titanium alloy bracket; preferably, ultrasonic cleaning is carried out in double distilled water, acetone and 75% ethanol for 30 minutes.
8. The preparation method according to claim 7, characterized in that: Step 1.2) Ti6Al4 V The metal is in the form of spherical powder with a diameter of 15 to 53 μm.
9. The preparation method according to claim 6, characterized in that: The specific steps of step 2) are: use a high-energy industrial integrated ultrafast amplified laser system with a pulse center wavelength of 532nm, a maximum output power of 18.7w, a repetition frequency of 180kH~220kH, a single pulse energy of 93.5μJ, a pulse width of 260fs, and a spot diameter of 3mm±1mm to perform femtosecond laser treatment on the titanium alloy porous bracket obtained in step 1) to obtain a 3D printed titanium alloy jaw bracket with a micro-nano surface structure.
10. An application of the titanium alloy jawbone stent according to any one of claims 1 to 5, characterized in that: Used as a repair material for oral and jaw bone defects.